2022
DOI: 10.3390/d14090753
|View full text |Cite
|
Sign up to set email alerts
|

Brachiopod Fauna from the Deep Mediterranean Sea: Distribution Patterns and Ecological Preferences

Abstract: Compared to their fossil counterparts, living brachiopods are investigated far less often, due to their occurrence in remote environments such as dark caves or deep environments. Due to the scarcity of studies targeting in situ brachiopods’ populations, large-scale information on their distribution and ecological preferences is still lacking, especially on hardgrounds. The extensive employment of remotely operated vehicles (ROVs), however, has opened up the chance to better explore this taxon’s diversity and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…The latitudinal/bathymetrical fluctuation of living brachiopods' OI should also reflect the habitats they live in today. According to field observations, most of the living brachiopods are inhabitants of relatively deep waters, cold polar regions, or cryptic habitats (e.g., submarine caves, crevices, overhangs on rock walls) where food resources and predators are limited (Bitner & Gerovasileiou, 2021; Peck, 2001; Toma et al, 2022; Zezina, 2008; Zuschin & Mayrhofer, 2009). This would mean that biotic interactions and especially predation activities would be limited in these cryptic “refuge‐type” habitats (Harper, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The latitudinal/bathymetrical fluctuation of living brachiopods' OI should also reflect the habitats they live in today. According to field observations, most of the living brachiopods are inhabitants of relatively deep waters, cold polar regions, or cryptic habitats (e.g., submarine caves, crevices, overhangs on rock walls) where food resources and predators are limited (Bitner & Gerovasileiou, 2021; Peck, 2001; Toma et al, 2022; Zezina, 2008; Zuschin & Mayrhofer, 2009). This would mean that biotic interactions and especially predation activities would be limited in these cryptic “refuge‐type” habitats (Harper, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Different colors from the pie chart indicate the proportion of OI (dark gray: with ornamentation, light gray: smooth).The latitudinal/bathymetrical fluctuation of living brachiopods' OI should also reflect the habitats they live in today. According to field observations, most of the living brachiopods are inhabitants of relatively deep waters, cold polar regions, or cryptic habitats (e.g., submarine caves, crevices, overhangs on rock walls) where food resources and predators are limited(Bitner & Gerovasileiou, 2021;Peck, 2001;Toma et al, 2022;Zezina, 2008;…”
mentioning
confidence: 99%
“…Their occurrence is well documented from Pleistocene white coral framestones (Remia and Taviani 2005). A recent study describing the distribution of large brachiopod species in the Ligurian Sea, Tyrrhenian Sea and the Sicily Channel indicates that M. truncata is today very abundant in the area of the Sciacca Banks, while T. retusa has a more northern distribution (Toma et al 2022c).…”
Section: The Past and Present Benthic Community Of Sciaccamentioning
confidence: 98%
“…No other bivalves, now commonly reported as associated with white coral habitats [e.g., Asperarca nodulosa (Müller, 1776)] (Taviani et al 2005), have been found, even if this could probably partially be related to the shallower depths of the Sciacca source population and the absence of a reef tridimensionality attracting a higher diversity of associated macrofauna (Rueda et al 2019). The recorded brachiopod species, Megerlia truncata and Terebratulina retusa, are known both from mesophotic depths and cold-water coral environments (Mastrototaro et al 2010;Toma et al 2022c).…”
Section: The Past and Present Benthic Community Of Sciaccamentioning
confidence: 99%
“…Over the last two decades, ROV (or other underwater vehicles and towed systems) exploration has proven to be a powerful method for investigating marine ecosystems, providing valuable insights into biodiversity, species distribution, habitat structure, and ecological dynamics i.e., [3,11,[51][52][53]. These technologies enable researchers to explore previously inaccessible or understudied habitats, unveiling new discoveries and expanding our understanding of marine ecosystems, primarily in the deep sea, allowing us to assess ecosystem health, identify vulnerable or threatened species, and evaluate the impacts of human activities.…”
Section: Introductionmentioning
confidence: 99%